Analisis Kejadian Tuberkulosis (TB) Paru - Evi Nopita; Lilis Suryani; Helen Evelina Siringoringo (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Indonesia ranks second in the world as the country with the highest number of TB sufferers after India. Pulmonary TB sufferers are in developing countries around 80% with 25% mortality rate or 1.7 million per year and 75% of TB sufferers are productive group (15-55 years old). This disease continues to spread even though it can be prevented. This research is a quantitative research with analytical survey method through cross sectional approach and involves as many as 76 respondents, conducted at the UPT Peninggalan Public Health Center, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province in May 2022. The analysis used the Chi-Square statistical test with a significance degree of p-value <0.05. The results of the study were obtained from 76 respondents, most of whom did not experience pulmonary TB incidence 46 (60.5%), most of them were of productive age 52 (68.4%), male 43 (56.6%), highly educated 40 ( 52.6%, knowledgeable 56 (73.7%), smoking status 54 (71.1%), no contact with 40 (52.6%), met the requirements for occupancy density 59 (77.6%) ), and had 65 ventilation (85.5%). There is a relationship between age (p-value = 0.045), gender (p-value = 0.032), education (p-value = 0.013), knowledge (p-value = 0.000), smoking status (p-value = 0.001), history of contact (p-value = 0.000), occupancy density (p-value = 0.007), ventilation (p-value = 0.021) with the incidence of pulmonary TB. Knowledge is the most influential factor (p-value 0,001). UPT Peninggalan Public Health Center, Tungkal Jaya district, Musi Banyuasin Regency can provide knowledge dissemination to the community regarding pulmonary TB by counseling, simulations and demonstrations, providing media such as brochures, billboards, banners, and involving various parties